DIPLOMATIC TERMINOLOGY AND ITS FUNCTIONAL USAGE - Munira Isroilovna Absamadova (International Journal of Literature and Language Studies, 2026)
Diplomatic language represents a highly specialized domain of institutional discourse characterized by precision, convention, and strategic ambiguity. The present study explores the theoretical foundations and functional usage of diplomatic terms within international communication, with particular emphasis on their pragmatic, semantic, and discursive dimensions. Drawing on approaches from lexicology, discourse analysis, and pragmatics, the article examines how diplomatic terminology operates not merely as a system of lexical units but as a tool for negotiation, conflict management, and international cooperation. The research highlights the inherent duality of diplomatic terms, which simultaneously convey explicit meaning and implicit intention. The findings suggest that diplomatic vocabulary is shaped by historical conventions, institutional practices, and cultural factors, and its usage reflects both linguistic norms and political objectives. The article contributes to a deeper understanding of how language functions in diplomacy and provides insights relevant to comparative linguistic studies, particularly between English and Uzbek diplomatic discourse.